EFFECT OF L-ARGININE SUPPLEMENTATION WITH ENDOTHELIAL FUNCTION IN DIABETES MELLITUS AND CARDIOVASCULAR DISEASE: AN EVIDENCE BASED CASE REPORT - Yusi Deviana; Diyah Eka Andayani (Perhimpunan Dokter Gizi Klinik Indonesia, 2022)
Abstract Background: Cardiovascular disease is the main complication that induces morbidity in diabetes mellitus patients. Endothelial function plays a role in these complications. Nitric oxide is a nitrogen-free radical produced from L-arginine, involved in several mechanisms for maintaining endothelial function to prevent cardiovascular disease and diabetes mellitus. Methods: A search for relevant literature in PubMed, Cochrane, and ProQuest was conducted. After assessing the relevancy and eligibility of the literature, two pieces of literature were selected and critically appraised. Results: There are two works of literature from systematic review and meta-analysis were found. The studies suggest pro and contra L-arginine supplementation with endothelial function in diabetes mellitus and cardiovascular disease. Conclusions: L-arginine might be the alternative supplement for cardiovascular disease and diabetes mellitus, but further analysis in improved studies is needed to confirm. Keywords: l-arginine, diabetes mellitus, cardiovascular disease, endothelial